P106 Pentameric, but not monomeric C-reactive protein, limits the snRNP-immune complex triggered type I interferon response: implications for lupus pathogenesis. (23rd March 2020) - Svanberg, Cecilia; Enocsson, Helena; Martinsson, Klara; Potempa, Lawrence; Rajab, Ibraheem; Wetterö, Jonas; Larsson, Marie; Sjöwall, Christopher
Abstract : Background: Systemic Lupus Erythematosus (SLE) is an autoimmune systemic disease affecting multiple organs and which is characterized by autoantibodies directed against nuclear constituents. Common autoantibody targets include double-stranded (ds) DNA and small nuclear ribonucleoproteins (snRNPs; i.e. U1-snRNP). Uptake of immune complexes (ICs) by plasmacytoid dendritic cells (pDCs) can activate endosomal toll-like receptors (TLRs) such as TLR-7 and TLR-9 if nucleic acids are present in the ICs. Such activation is dependent on IC internalization by Fcγ receptor type IIa (FcγRIIa), and results in production of type I interferons (IFNs), a hallmark of SLE and a target for therapeutic interventions. The acute phase protein C-reactive protein (CRP) binds FcγRs, as well as some nuclear proteins, including snRNPs. Pentameric (native) CRP has previously been suggested to inhibit production of IFNs in peripheral mononuclear cells (PBMCs) in response to ICs formed by autoantibodies against snRNP, an effect which was further investigated herein. Methods: PBMCs or magnetically (MACS) purified pDCs were retrieved from whole blood of healthy volunteers. Type I IFN gene transcription and production was stimulated by addition of snRNP containing ICs ± pentameric CRP (pCRP) or monomeric CRP (mCRP) in different sequential order. IC formation was achieved through simultaneous addition of snRNP and bulk IgG, retrieved from an SLE patient with high levels of snRNP autoantibodies, directly to the cells. Type I IFNs and inflammatory cytokines were investigated using quantitative PCR, ELISA and cytometric bead array, and cells responsible for production of the IFNs were characterized using flow cytometry. For statistics a two-tailed t-test was performed. Results: pCRP had an inhibitory effect on the IFN gene expression in PBMCs after incubation with ICs, p=0.044 for IFNα4 and p=0.047 for IFNβ at the 4h time-point compared to IC only. pCRP also showed a dose-dependent inhibitory effect on the type I IFN production in the cells. The monomeric form of CRP showed modest or no effect on IFN levels, p=0.82 for IFNα4 and p=0.58 for IFNβ at the 4h time-point compared to IC only. A pre-incubation of the cells with pCRP increased the inhibitory effects compared to simultaneous addition of pCRP and ICs, suggesting that initial binding to the cells is a critical step for inhibition. Flow cytometry suggested that pDCs are the main producer of the type I IFNs. In addition, pCRP seems to have a more general inhibitory effect on type I IFNs, as seen in the reduction of IFN production in response to the TLR-9 ligand CpG. Conclusions: pCRP has a distinct inhibitory effect on type I IFNs, which is largely not seen for the dissociated form of CRP (mCRP). The more general inhibitory effects shown by pCRP highlights its immune regulatory function in pathologies characterized by high production of type I IFNs. The identity of the initial receptors responsible for pCRP mediated effects, as well as of the involved signaling pathways, will be further investigated.